LAJU PERNAFASAN IBU DENGAN GANGGUAN SOMATISASI YANG DIBERIKAN TERAPI RELAKSASI AUTOGENIK - Desiyani Nani (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACTSomatization disorders often experienced by mothers who have children with special needs. Complaints are often accompanied by disturbances of perceived physical condition and sometimes it does not. Respiratory rate as vital signs describes body's response to stress condition. Autogenic relaxation technique is one of the therapeutic modalities available for the prevention of somatization disorder, namely by auto-suggestion or self- suggestion so relaxed state is reached. This study aims to identify the effect of relaxation therapy on the frequency of respiratory autogenic mothers who have children with special needs. The study design used was a non randomized experiment Quasy pretest-posttest with control group design. Number of Samples 29 respondents who were counted respiratory rate before and after autogenic relaxation therapy for 3 days . The test data was statistics Wilcoxon test and Mann-Whitney. The results showed no significant difference between the respiratory rate in the intervention group and the control group with p = 0.329 (p>0.05). There is no difference in respiratory rate between the intervention group and the control group. Keywords : somatization disorder , autogenic therapy , respiratory rate Kesmasindo, Volume 6( 2) Juli 2013, Hal 150-156